Driving a 3 Dof Robotic Manipulator with Protected Data Through Industrial Communication Using Master-Slave Architecture - Urrea-Onate, E (Institute of Electrical and Electronics Engineers Inc., 2019)
This paper deals with the design, implementation and assessment of an error tolerant industrial communications based on master/slave architecture applied to a 3 DOF manipulator robot. Algorithms for implementing communication between coding and decoding systems based on Hamming code (7.4) are developed. Communication tests are conducted using the Python minimal Modbus and Modbus-tk libraries. The implementation of the communication hardware between the coding, decoding and 3 DOF manipulator robot are presented, using pcDuino and expander Pi cards. © 2019 IEEE.